If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2 = 3x + -15 + 9 Reorder the terms: 2 + 2x = 3x + -15 + 9 Reorder the terms: 2 + 2x = -15 + 9 + 3x Combine like terms: -15 + 9 = -6 2 + 2x = -6 + 3x Solving 2 + 2x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 2x + -3x = -6 + 3x + -3x Combine like terms: 2x + -3x = -1x 2 + -1x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -1x = -6 + 0 2 + -1x = -6 Add '-2' to each side of the equation. 2 + -2 + -1x = -6 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -6 + -2 -1x = -6 + -2 Combine like terms: -6 + -2 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8
| 50x+20=8(40) | | 2x-11=7x | | 2x-11=7c | | 6st*2st*t*t*t= | | 0.7z-11.9=-0.3z+0.15 | | 3a-4=2 | | 36-3(4r-8)=0 | | 247*.50= | | 14-2n= | | 1x+4y=-4 | | 0.5x+10=2.4x+3.4 | | 14a+16b+3c+5c-2b-6a= | | 5(x-6)=26-2x | | 10-(6)=2x | | X+x+1+x+2+x+3=132 | | 6x-4=74-7x | | (x-5)(-3x+7)-(x-5)=0 | | -17=-8 | | x^2+6x=x+3 | | 5y-6=2y+10 | | (X+8)+x=6 | | 8+2(x-2)=8 | | 6s-2t+3+7s+5t-9= | | 5x+39= | | 37+w=5w-2 | | X=2y-550 | | 9x+15=(3x+5) | | (8+10)-10=2x | | 2x-5y=-24 | | (X+8)+x=8 | | 3(e+1)=2(e-5) | | 84x^3-84x^2+84x-84=0 |